EFEKTIVITAS EKSTRAKURIKULER PRAMUKA SELAMA PANDEMI COVID-19 DI SMA NEGERI 1 NGAWEN - Sinta Tri Noviana; Rifiana Febriyanti; Main Sufanti; Gallant Karunia Assidik (Buletin Literasi Budaya Sekolah, 2021)
This study aims to look at the scout extracurricular activities during the corona virus pandemic. The problems in this research are extracurricular activities during the pandemic and the effectiveness of scout extracurricular activities during a pandemic at SMA Negeri 1 Ngawen. The methods used are quantitative and qualitative descriptions. Data collection was carried out by observation, interviews, and distributing questionnaires. After the data is obtained, the data will be analyzed inductively, then validated using triangulation techniques. The results showed that the implementation of scout extracurricular activities during the Covid-19 pandemic at SMA Negeri 1 Ngawen was carried out online using Microsoft Office 365 media. This online Scout extracurricular could be in the form of delivery of scouting and production materials taken from quizzes, practical videos, and student activeness in class. X. The effectiveness of this scout extracurricular can be in the form of time use and understanding of students in understanding the scout material. From levels 1-5, it can be concluded that extracurricular implementation during the pandemic ranges at level 4, which is said to be good with a percentage of 48.6%.